La escucha activa: perspectivas teóricas y enfoques multidisciplinarios = Abweichender Titel: Active Listening : Theoretical Perspectives and Multidisciplinary Approaches - Ruiz Valeros, Maria Ángeles (Cauriensia, 2025)
This article examines the phenomenon of listening from a communicative and humanistic perspective, questioning the widespread use of the term "active listening" and reclaiming listening as a constitutive dimension of human relationality. Through a multidisciplinary approach-integrating contributions from psychology, pedagogy, sociology, and the arts-and supported by a critical literature review on active listening, the study analyses its role in the construction of social identity, cognitive and emotional development, and the quality of interpersonal bonds. It also explores its implications for mental health, care practices, and social support initiatives such as the Telephone of Hope. The findings indicate that listening and silence hold formative and relational value that goes beyond technical skill, emerging as attitudes of presence, recognition, and care. Overall, the article argues for a renewed understanding of listening as a transversal competence and an ethical mode of encounter that sustains dialogue, coexistence, and attention to human vulnerability.